Carbonation induced corrosin analysis of reinforced concrete structure based on full probabilistic approach - an Indonesian case study / Herry Prabowo and Mochamad Hilmy - Herry, Prabowo; Mochamad, Hilmy (Universiti Teknologi MARA, Perak, 2018)
The assessment of the service life of concrete structures using the durability design approach is widely accepted nowadays. It is really encouraged that a simulation model can resemble the real performance of concrete during the service life. This paper investigates the concrete carbonation through probabilistic analysis. Data regarding Indonesian construction practice were taken from Indonesian National Standard (SNI). Meanwhile, data related to Indonesian weather condition for instance humidity and temperature are taken from local Meteorological, Climatological, and Geophysical Agency from 2004 until 2016. Hopefully the results can be a starting point for durability of concrete research in Indonesia.